2020
DOI: 10.1111/crj.13269
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of and six‐month adherence to continuous positive airway pressure in patients with moderate to severe obstructive sleep apnea

Abstract: Background Continuous positive airway pressure (CPAP) is the most effective treatment for moderate to severe obstructive sleep apnea (OSA). Acceptance of and adherence to CPAP are crucial for optimal treatment outcomes. The aim of this study was to investigate the factors influencing patients’ acceptance of and adherence to CPAP treatment. Methods One hundred eighty‐eight patients with moderate to severe OSA who had received CPAP titration from October 2017 to September 2018 were recruited. They were interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…In this study, the AHI, RDI, ODI, and AI values were higher in the adherent group, and the nadir SpO 2 was lower, suggesting that OSA was more severe, which is consistent with the results of previous studies. However, there was no significant difference between the patient groups in subjective sleep-related symptoms measured using the PSQI and KESS before treatment, which is also consistent with the results of previous studies [ 2 , 23 ]. However, some studies have reported that changes in sleep symptoms before and after treatment are related to adherence [ 2 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the AHI, RDI, ODI, and AI values were higher in the adherent group, and the nadir SpO 2 was lower, suggesting that OSA was more severe, which is consistent with the results of previous studies. However, there was no significant difference between the patient groups in subjective sleep-related symptoms measured using the PSQI and KESS before treatment, which is also consistent with the results of previous studies [ 2 , 23 ]. However, some studies have reported that changes in sleep symptoms before and after treatment are related to adherence [ 2 ].…”
Section: Discussionsupporting
confidence: 91%
“…There were no significant differences in age, BMI, underlying diseases, or subjective symptoms. Although sex has been mentioned as a factor influencing adherence to PAP, several studies have not shown consistent results [ 2 , 4 ]. In the case of height, it could not be ruled out that the result was due to the difference in the male to female ratio in each patient group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review found that CPAP machine treatment gained incremental cost–effectiveness ratios of 16,499 USD with a maximum of 33,119 USD per quality-adjusted life years. Generally, patients with OSA had an acceptance rate for CPAP machine treatment of 48.6–60% [ 45 , 46 ]. The CPAP machine acceptance rate may be higher in some specific population such as Down syndrome (92% after 1 month trial) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study had the average age of 53.86 years which may have higher rate of CPAP machine purchasing. However, this study did not have any interventions which may facilitate CPAP machine acceptance and purchasing such as disease awareness education, comfortable titration experience, or short-term home CPAP trial [ 45 ]. A study from Singapore found that a 1-month CPAP trial may also increase CPAP adherence to 78.5% [ 52 ].…”
Section: Discussionmentioning
confidence: 99%